Pemilihan Karyawan Terbaik Pada PT. Shippindo Teknologi Logistik Dengan Metode Analytical Hierarchy Process (AHP) - Prasetyo, Raka; Riska, Riska; Erdiana, Novita Putri (TIN: Terapan Informatika Nusantara, 2022)
In determining the best employees who are skilled and able to contribute to the success of the company, it is necessary to evaluate work performance for all forms of work that have been carried out by these employees. The results of work performance can be used as an opportunity for employees and companies to see the potential from the internal side. From these results, the company can have and see the best employees from all existing employees. And from the employee's point of view, seeing the potential to get rewards from the achievements they make, so that the selection of the best employees becomes a passion for employees and improving work quality. The AHP method is the most widely used because the method is conceptually simple, easy to understand, computationally efficient, and can measure the performance of decision alternatives in a simple mathematical form. Data was collected using interviews, observations, and literature studies. From these results obtained the order of the best employees including Sigit Purnomo ranks first with a percentage of 24.76%, Ajat Rusmanto ranks second with a percentage of 23.99%, Nursan ranks third with a percentage of 19.01%, Taufik Solehudin ranks fourth with a percentage of 17.53%, and Dede Kurniadi ranks fifth with a percentage of 14.71%. The results of the study using the Analytical Hierarchy Process (AHP) method placed Ajat Rusmanto as the best packing operator